Seasonal size distribution of Anacroneuria (Plecoptera: Perlidae) in an andean tropical river - BOHÓRQUEZ, HUGO; REINOSO, GLADYS; GUEVARA, GIOVANY (Revista Colombiana de Entomología, 2011)
Total body length and head capsule width (mm) were used as biometric characteristics in discriminating between size-frequency estimates of three Anacroneuria morphospecies, from 28 sampling sites along a tropical river subject to bimodal variations in water level in Central Colombia. A total of 344 specimens grouped into four size classes were collected. The highest abundance of Anacroneuria larvae was observed during the dry season and there was a higher abundance of small-sized individuals (body length